Between borders the great Jewish migration from Eastern Europe - !717321312!Brinkmann, Tobias *1967-* ; ID: gnd/1022870408 (Oxford University Press, 2024)
Between Borders tells and contextualizes the stories of these Jewish migrants and refugees before and after the First World War. It explains how immigration laws in countries such as the United States influenced migration routes around the world. Using memoirs, letters, and accounts by investigative journalists and Jewish aid workers, Tobias Brinkmann sheds light on the experiences of individual migrants, some of whom laid the foundation for migration and refugee studies as a field of scholarship.